THE INFLUENCE OF INTELLECTUAL INTELLIGENCE, EMOTIONAL INTELLIGENCE, SPIRITUAL INTELLIGENCE ON THE PERFORMANCE OF EMPLOYEES OF THE FIRE AND RESCUE SERVICE OF SURABAYA CITY: PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL TERHADAP KINERJA KARYAWAN DINAS PEMADAM KEBAKARAN DAN PENYELAMATAN KOTA SURABAYA - Dewie Tri Wijayati Wardoyo; Rian Dwi Cahya; Anang Kistyanto (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This study aims to analyze the influence of intellectual intelligence, emotional intelligence, and spiritual intelligence on the performance of fire department employees in the firefighting division of Surabaya. Employee performance is a crucial aspect of a fire department organization, as the success of the team in handling emergency situations depends on the effectiveness, resilience, and quick response of each individual. This research employs a quantitative method by collecting data through questionnaires distributed to 100 employees of the Surabaya Fire Department. Based on the analysis results, it was found that intellectual intelligence (X1) and emotional intelligence (X2) did not have a significant influence on employee performance, with t-values of 1.422 and 0.646, respectively, which were smaller than the t-table value of 1.69, and p-values of 0.159 and 0.520, respectively, which were larger than 0.05. On the other hand, spiritual intelligence (X3) was proven to have a significant effect on employee performance, with a t-value of 8.163 larger than the t-table value of 1.69 and a p-value of 0.000 smaller than 0.05. The findings of this study highlight the importance of spiritual intelligence in improving employee performance, particularly in situations that require resilience, motivation, teamwork, and ethical decision-making. This research suggests the importance of developing spiritual intelligence as part of performance enhancement strategies in the workplace of fire departments.